P174 Transmembrane TNF transgenic mice exhibit enlarged lymph nodes and elevated numbers of high endothelial cells associated with increased lymphocyte recruitment. (March 2019) - Jeucken, KC; van Hamburg, JP; Kaaij, MH; van Duivenvoorde, LM; Baeten, DL; Tas, SW
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: NF-κB signaling plays a crucial role in chronic inflammatory diseases and can be activated via two pathways. Noncanonical NF-κB signaling can be induced by different signals, including transmembrane (tm)TNF ligation to TNF receptor 2 (TNFR2), which is restricted to specific cell types including endothelial cells (EC). Activation of the noncanonical NF-κB pathway in EC is involved in differentiation into high endothelial cells (HEC), which make up specialized high endothelial vessels (HEV) that recruite lymphocytes into lymph nodes (LN). tmTNF transgenic (tg) mice overexpressing tmTNF develop chronic inflammatory features, including arthritis and axial inflammation. Objectives: To study LN size and composition, including stromal cell and lymphocyte subsets in tmTNF tg mice. We hypothesized that overexpression of tmTNF results in increased noncanonical NF-κB signaling in HEC leading enhanced lymphocyte recruitment. Methods: Peripheral (PLN) and mesenteric LN (MLN) of 7 week old tmTNF tg mice and age-matched wild types (WT) were collected, dissected and analyzed using flow cytometry. Cellular markers were used to distinguish between different EC subsets, and B and T lymphocytes. Results: Lymph nodes of tmTNF tg mice had more than two-fold increased total cell numbers compared to WT (PLN: 23, 7*10 6 ±7, 9*10 6 ; MLN: 24, 9*10 6 ±5, 3*10 6 . WT PLN: 5, 2*10 6 ±1, 0*10 6 ; MLN: 10, 4*10 6 ±4, 6*10 6 ). Total numbers of HEC in tmTNF tg mice LN were increased (PLN: 2, 3*10 3 ±0, 50*10 3 ; MLN: 1, 9*10 3 ±0, 64*10 2 . WT PLN: 714±393; MLN: 1.199±506), as were capillary EC (CEC) numbers (PLN: 2067±42; MLN: 2425±71. WT PLN: 1097±609; MLN: 1327±230). Notably, HEC:CEC ratio was increased in tmTNF tg mice (PLN: 1, 10±0241. WT PLN: 0, 66±0, 006). In addition, total B and T lymphocytes in tmTNF tg mice LN were strongly increased (B lymphocytes: PLN: 10, 2*10 6 ±3, 5*10 6 ; MLN: 10, 9*10 6 ±1, 8*10 6 . WT PLN: 2, 8*10 6 ±5, 8*10 5 ; MLN; 5, 8*10 6 ±2, 4*10 6 . T lymphocytes: PLN: 12, 8*10 6 ±4, 5*10 6 ; MLN: 14, 2*10 6 ±2, 8*10 6 . WT PLN: 2, 5*10 6 ±3, 8*10 5 ; MLN: 4, 7*10 6 ±2, 1*10 6 ). Conclusions: Overexpression of tmTNF in mice leads to an increase in total HEC, CEC and lymphocyte numbers and an increased HEC:CEC ratio in PLN and MLN. The increase in HEC may be the result of enhanced noncanonical NF-κB signaling, enhancing lymphocyte recruitment into the LN. Consequently, interfering with noncanonical NF-κB signaling in EC may be a promising treatment strategy to dampen inflammation in immune-mediated inflammatory diseases, which is the subject of current studies. Disclosure of Interest: None declared.